Nurse Leaders Employ Contemplative Practices to Promote Healthcare Professional Well-being and Decrease Anxiety. (March 2021) - Cunningham, Tim; Çayir, Ebru
Abstract : Supplemental digital content is available in the text. Abstract : OBJECTIVE: The purpose of this study was to test the effectiveness of a daylong resilience retreat on healthcare professionals' anxiety levels, intention to engage in mindfulness practices, and self-efficacy around mindfulness. BACKGROUND: Caregiver burnout is a concern that needs to be addressed at the organizational level so that professionals can reduce their risk of psychological injury while providing high-quality care. The COVID-19 (novel coronavirus) pandemic has exacerbated symptoms of burnout among nurses nationally. METHODS: Ten sessions of daylong resilience retreats were delivered to independent groups of nurses, nurse practitioners, and other healthcare professionals. Preretreat and postretreat assessments were completed using a 19-item survey developed by the research team to assess state anxiety, intention to engage in mindfulness practices, and self-efficacy around mindfulness. RESULTS: One hundred six healthcare professionals completed the resilience retreats. There was a statistically significant decrease in state anxiety scores following the retreat. The majority of the participants reported high intentions to engage in mindfulness practices and felt confident about incorporating mindfulness in their lives. CONCLUSIONS: Brief resilience retreats endorsed by nurse leadership can reduce perceived anxiety and facilitate engagement in contemplative practices, which are associated with a decrease in the risk of burnout.